2019
DOI: 10.1093/mnras/stz719
|View full text |Cite
|
Sign up to set email alerts
|

Radio forensics could unmask nearby off-axis gamma-ray bursts

Abstract: The multi-messenger observation of gamma-ray burst (GRB) 170817A from the nearby binary neutron-star merger GW170817 demonstrated that low-energy γ-ray emission can be observed at relatively large angles from GRB jet axes. If such structured emission is typical, then the currently known sample of short GRBs with no distance measurements may contain multiple nearby off-axis events whose delayed afterglows could have gone undetected. These nearby neutron star mergers may produce telltale radio flares peaking yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 104 publications
(161 reference statements)
2
29
1
Order By: Relevance
“…). One natural way for this to happen is if these GRBs are viewed slightly off-axis from the cores of their jets (see e.g., Bartos et al 2019;Mandhai et al 2019;Dichiara et al 2020).…”
Section: Exceptional Grbsmentioning
confidence: 99%
“…). One natural way for this to happen is if these GRBs are viewed slightly off-axis from the cores of their jets (see e.g., Bartos et al 2019;Mandhai et al 2019;Dichiara et al 2020).…”
Section: Exceptional Grbsmentioning
confidence: 99%
“…Radio flares from neutron star mergers thus remain an outstanding possibility yet to be discovered, not just for GW170817 but for any merger. A successful observation requires a nearby event within 200 Mpc (Hotokezaka et al 2016), much closer than short GRBs identified so far other than GW170817 (albeit this could be due to selection effects (Bartos et al 2019;Gupte & Bartos 2018)), and a circum-merger density of 10 −2 cm −3 , greater than the density for GW170817 and many other short GRBs (Fong et al 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Taking the second observation to be VLASS epoch 2, which was taken to occur 32 months after epoch 1 and have the same sensitivity of 120 µJy, we found that only 2.5 +8.2 −2.3 neutron star mergers will appear as transients, making this strategy risky. Therefore, we considered a targeted VLA followup of radio sources, with observations taking place during the summer of 2021, and assuming a sensitivity of 3 µJy (Bartos et al 2019). We found that such a targeted follow-up will be able to establish 17 +56 −15 radio signals to have originated from neutron star mergers.…”
Section: Detection Rate Estimation Using the Vlass Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…One natural way for this to happen, is if these GRBs are viewed slightly off-axis from the cores of their jets (see e.g. Beniamini et al 2019b;Mandhai et al 2019;Bartos et al 2019;Dichiara et al 2019).…”
Section: Exceptional Grbsmentioning
confidence: 99%